Glory to Dazhboh (Sun-god) or to All Native Gods? Monotheism and Polytheism in Contemporary Ukrainian Paganism - Lesiv, Mariya (Pomegranate, 2010)
Contemporary Ukrainian Pagans offer an alternative way of constructing a distinct national identity, based on old Slavic traditions, during times of socio-political turmoil. Despite some unifying characteristics, including nationalist views, there are many groups whose doctrines differ markedly. One of the major polemics is connected with the notions of monotheism versus polytheism as the basis for a contemporary Ukrainian spirituality. The debate between polytheism and monotheism, related to creative interpretations of the largely unknown past and dissimilar visions of the future, forms the main focus of this article. Polytheism and monotheism are often viewed as antagonistic categories. Moreover, some scholars argue against these terms, emphasizing their modern origins and strong political connotation. They are viewed as anachronistic when applied to complex and shifting spiritual practices, especially in ancient contexts. In contrast to this, Ukrainian Paganism shows that these antagonistic models can sometimes coexist, although in debate with each other, in the complex process of identity formation even within the same religious movement. While old Slavs likely did not think about themselves in these terms, their present-day Ukrainian counterparts consciously embrace “monotheism” and “polytheism” as modern political categories. In fact, these categories help Ukrainian Pagans to negotiate (among themselves) the best way to build a “pure” national identity. Monotheistic Pagans associate monotheism with the evolutionist idea of “progress” while polytheists emphasize the “authenticity” of their own worldview. Indigenized in this way, “monotheism” and “polytheism” are valid terms for describing contemporary ideologies.